Impact of maternal iron deficiency on cortisol levels and auditory brainstem responses in the young and adult guinea pig - Shero, Nora (Université d'Ottawa / University of Ottawa, 2017)
Maternal iron deficiency is a world wide and major public health issue. Despite recent researchers’ interest related to this topic, its impact in the offspring still remains unclear. The aim of this study is to understand the impact of maternal iron deficiency on the auditory functions and serum cortisol levels in the young and adult guinea pig at post-natal day (PNd) 24 and PNd84, respectively. Pregnant guinea pigs were given an iron deficient (ID) or iron sufficient (IS) diet during gestation and lactation. An iron sufficient diet was provided to all pups after weaning day. No significant difference was observed in the hearing threshold and latencies in siblings from both groups at PNd24 and PNd84. However, ID offspring showed a significant higher interpeak latency I-IV at 100 dB than IS pups at PNd24. ID offspring also had significant elevated cortisol levels at PNd24 compared to IS control group. Maternal iron deficiency affects negatively the auditory functions and raises the serum cortisol levels, a biomarker of stress in the offspring.
Keywords: Maternal iron deficiency; Serum cortisol; auditory brainstem response; hyperactivity